Historical Writing in Britain, 1688-1830
X, 228 p.
Keywords: Historical Writing in Britain, 1688-1830 explores a series of debates concerning the nature and value of the past in the long eighteenth century. The essays investigate a diverse range of subjects including art history, biography, historical poetry, and novels, as well as addressing more conventional varieties of historical writing.